A Method of Extended Jacobian and Firefly Algorithm for the Kinematic Analysis of Planar Robots - T. Raja Prathab; R. Suja Mani Malar; T. Ahilan (IAES International Journal of Robotics and Automation (IJRA), 2017)
Planar robots are one of the optimal robot form impacted in typical Cartesian plane. It consists of fixed divisions and connectors positioned in series which offers like working of human arm. The one end of robot arm position is fixed and the other arm of the robot move through the Cartesian plane by modifying the framework of arm joints. The kinematic analysis on planar robot includes position, velocity and acceleration are validated not by considering the force which cause motion to robot. The manipulator with lack of design and fault tolerant operation is analytical for application in remote and threat environment where periodic maintenance and improvements are not available. The most advanced architecture and operational flexibility of robots offer new probability and advancement in a large scale of fabrication process. This paper proposes inverse kinematic analysis of PUMA 560 robotic arm to conclude long range of fault tolerance. The proposed work incorporates Jacobian and Firefly algorithm are generally useful for determining inverse kinematics for redundant robots.